Experimental study of new pyrazolo[3,4-D]pyrimidine-4-one derivatives for anticonvulsant activity spectrum - Каврайський, Дмитро Павлович; Штриголь, Сергій Юрійович; Георгіянц, Вікторія Акопівна; Северіна, Ганна Іванівна (ScienceRise: Pharmaceutical Science, 2016)
Aim. To determine an effective dose range of three compounds of pyrazolo[3,4-d]pyrimidin-4-one derivatives in a basic pentylenetetrazole-induced seizure model and spectrum of anticonvulsant activity in experimental models of seizure with different pathogenetic mechanisms. Materials and methods. The experiments were performed on 240 mature albino male mice weighing 19–29 g. The dose dependence was investigated on a basic screening model of pentylenetetrazole-induced seizures on mice. Mice were exposed to electrical stimuli lasting for 0.2 s (50 Hz, 50mA) using corneal electrodes in another conventional maximal electroshock seizure model. A neurotransmitter profile of the leading compound effect was determined in picrotoxin-, thiosemicarbazide, strychnine- and caffeine-induced seizure models. Compounds and reference-drug were administered intragastrically 30 min before a subcutaneous (for picrotoxin and strychnine) or an intraperitoneal (for caffeine and thiosemicarbazide) convulsant administration. Results. Compound 78553 (200 mg/kg) and compound 78342 (100 mg/kg) have demonstrated the most marked anticonvulsant properties in the pentylenetetrazole-induced seizure model which effects are comparable to those of valproate sodium (300 mg/kg). Only compound 78553 (1-(4-metoxyphenyl)-5-{2-[4-(4-metoxy-phenyl)piperazine-1-yl]-2-oxoethyl}-1,5-dihydro-4H-pyrazole[3,4-d]pyrydine-4-one) had a moderate anticonvulsant effect in maximal electroshock seizure test. In seizure models with different pathogenetic mechanisms the compound 78553 has demonstrated an obvious effect on caffeine-induced seizures, moderate effect on picrotoxin-induced seizures (at relatively low dose of anticonvulsant), and insignificant effect on strychnine-induced seizures. Conclusions. The spectrum of anticonvulsant activity results of the leading compound 78553 in the seizure models with different pathogenesis has shown its potential mechanisms to include a stimulated effect on GABAergic processes (antagonism to pentilenetetrazole), as well as antagonism to blocking GABA-activated chloride channels (moderate antagonism to picrotoxin), on the adenosinergic link (marked antagonism to caffeine) and on the neural membrane permeability to sodium (moderate reduction of a maximum electroconvulsive seizure). Glycinergic action (moderate antagonism to strychnine convulsive effect) may play a minor role. The study compound has produced no effect on thiosemicarbazide-induced seizures